Microglial activation is associated with vasoprotection in a rat model of inflammatory retinal vasoregression - Riemann, Sarah; Kolibabka, Matthias; Busch, Stephanie; Lin, Jihong; Hoffmann, Sigrid; Gretz, Norbert; Feng, Yuxi; Wohlfart, Paulus; Hammes, Hans-Peter (Frontiers in physiology, 2021)
Vascular dysfunction and vasoregression are hallmarks of a variety of inflammatory central nervous system disorders and inflammation related retinal diseases like diabetic retinopathy. Activation of microglia and the humoral innate immune system are contributing factors. Anti-inflammatory approaches have been proposed as therapies for neurovascular diseases, which includes the modulation of microglial activation. The present study aimed at investigating the effects of microglial activation by clodronate-coated liposomes on vasoregression in a model of retinal degeneration. Clodronate treatment over 5 weeks led to an increase in activated CD74+ microglia and completely prevented acellular capillaries and pericyte loss. Gene expression analyses indicated that vasoprotection was due to the induction of vasoprotective factors such as Egr1, Stat3 and Ahr while expression of pro-inflammatory genes remained unchanged. We conclude that activated microglia lead to a shift towards induction of pleiotropic protective pathways supporting vasoprotection in neurovascular retinal disease.
Gesehen am 29.05.2021